(untitled) (Journal of the College of Basic Education, 2022)
The study includes the collection of 70 burns and wound swabs from patients of different hospitals, in Baghdad area, for the period from November 2013 to February 2014 , 31 isolates characterized as Pseudomonas aeruginosa 9 (45%) from wound and 22 (78.57%) from burn swabs ,depending on the characteristics of the colonies phenotypic and microscopic when grown in differential selective media, as well as biochemical tests to diagnose isolates, Then the identification of these species were confirmed by using the system (GN I Card) using Vitek 2 device complementary step . The study includes sensitivity test towards 16 antibiotics for each species by using the system (AST Card) using Vitek 2 device, and the isolates ware Multi drug resistance , As results all isolates were resistant by 100 % for each of Piperacillin, Ticarcillin, Ticarcillin clavoulanic acid, Cefazolin, Ceftriaxone and Tigecycline . All strains were less resistance to Ceftazidime with percentage 50% , The minimal inhibitory concentrations (MICs) of some antibiotics were determined by using the system Vitek 2 device ,and the result determined as (R: resistance and S: sensitive